EKSPLORASI JENIS DAN PEMANFAATAN TUMBUHAN OBAT PADA MASYARAKAT DESA INDARI HALMAHERA SELATAN - Laswi Irmayanti; Jaetun Rasyid; Muhammad Nur; Saipul Riyadi (Universitas Lambung Mangkurat, 2021)
One of the community who have hereditary uses traditional medicine in the form of herbs is the Indari village community, West Bacan District, South Halmahera Regency, North Maluku. Until now, there has been no study regarding the types and parts of plants used for traditional medicine in Indari Village. The purpose of this research was to describe the types of plants and their parts that were commonly used as traditional medicine by Indari villagers. The data was clloected by means of an explorative survey, namely interviews and direct observations in the field. Interviews were aimed at custom leader, sandos/healers, as well as people who used or were familiar with medicinal plants. The results showed that there were 18 types of plants used by the Indari community as traditional medicine. These types namely Mengkudu (Morinda citrifolia), Jarak merah (Jatropha gossypifolia L), Kapas (Gossypium hirsitum), Gandarusa (Justicia gendarussa), Awar–awar (Ficus septica), Ketapang (Terminalia catappa), Waru (Hibiscus tiliaceus), Sirsak (Annona muricata), Kembang pukul empat (Mirabilis jalapa), Mahkota dewa (Phaleria macrocarpa), Kelapa (Cocos nucifera), Tapak kuda (Ipomoea pescaprae), Kedondong (Spondias dulcis P.), Langsat (Lansium domescitum), Mangga (Mangifera indica), Turi (Sesbania grandiflora), Mayana (Coleus artopurpureus), dan Kumis kucing (Orthosiphon aristatus). Plant organs were used are leaves, fruit, roots, bark, stems and leaves. Plant organs that are often used were the leaves.